Student's Reading Literacy: Opportunities and Characteristic for Instructional Media Development - Novela, Greria Tensa; Asrowi, Asrowi; Widyastono, Herry (Universitas Pendidikan Ganesha, 2022)
In this digital era, it seems that printed book readers are starting to shift to digital book readers through electronic devices, new technology has brought great benefits and opportunities in terms of getting information more quickly and efficiently. This study aims to analyze students' reading ability and the characteristics of the media needed to facilitate students' reading activities. This study used a qualitative descriptive research design, with a sample of 100 high school students. The technique of collecting data is through a questionnaire with the instrument consisting of questions that refer to the indicators of PISA questions to find out what difficulties students face in doing the PISA test, the results of the questionnaire are then analyzed descriptively using percentages. The results showed that the overall level of students' reading ability was still relatively low, through the questionnaire it was also shown that students were very interested in developing a learning media, with one of the prominent characteristics of the media being interactive. Therefore, students need an innovation in the form of developing learning media that contains certain characteristics according to the times so that it can be used as a means to facilitate students in activating reading skills. reading skills and reading interest.